2018
DOI: 10.1186/s12889-018-5692-2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and physical activity in asylum seekers in Northern England; using the theoretical domains framework to identify barriers and facilitators

Abstract: BackgroundMany asylum seekers have complex mental health needs which can be exacerbated by the challenging circumstances in which they live and difficulties accessing health services. Regular moderate physical activity can improve mental health and would be a useful strategy to achieve this. Evidence suggests there are barriers to engaging black and minority ethnic groups in physical activity, but there is little research around asylum seekers to address the key barriers and facilitators in this group.MethodsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 23 publications
(26 reference statements)
3
26
0
2
Order By: Relevance
“…We are well aware that due to one group pre-test/post-test design and the lack of random assignment, the results of our study must be interpreted with caution. While randomized controlled trials are needed for an advanced evidence base, researchers should be aware that the implementation of such studies will be complicated by multiple knowledge barriers and environmental constraints [52].…”
Section: Discussionmentioning
confidence: 99%
“…We are well aware that due to one group pre-test/post-test design and the lack of random assignment, the results of our study must be interpreted with caution. While randomized controlled trials are needed for an advanced evidence base, researchers should be aware that the implementation of such studies will be complicated by multiple knowledge barriers and environmental constraints [52].…”
Section: Discussionmentioning
confidence: 99%
“…More speci cally, previous research has established that people with severe mental ill health are less likely to engage in PA and are more sedentary in comparison to the general population [41,42]. Given the high rates of trauma-related ill health [3,4], disrupted daily life and work routines from home country [4,6], as well as other barriers to engage in PA that are likely to be faced by forced migrant populations, such as economic strain, access to facilities, and lack of motivation when living under extreme stress and uncertainty about the future [25,43,44], it may be concluded that asylum seekers are more readily susceptible to insu cient PA. An increased focus on assessment and promotion of PA is thereby justi ed. Moreover, recent research [45] has demonstrated important health bene ts even at much lower doses than advocated by generic PA guidelines, especially when moving from completely inactive to some activity [46], suggesting that the promotion of any level of PA may be advisable among those currently inactive or at the lower end of the insu cient PA spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…También se menciona que el ejercicio físico permite a las personas llevar a cabo actividades cotidianas sin fatigarse (Malina & Katzmarzyk, 2006). A diferencia del ejercicio físico, la actividad física como caminar más rápido y aumentar la intensidad del trabajo, puede ayudar a cambiar el estilo de vida (Haith-Cooper, Waskett, Montague, & Horne, 2018). Según el American College of Sports Medicine 2000, los términos ejercicio físico y actividad física sostienen una similitud importante entre ellos.…”
Section: Ejercicio Físicounclassified
“…Por otra parte, otros autores argumentan que, pese a los beneficios conocidos sobre la actividad física, un 30% de la población mundial no alcanza los niveles de actividad física recomendados (Franco et al, 2015). En cuanto a los efectos de bienestar psicológico y satisfacción con la vida, las personas que realizan actividad física con mayor frecuencia muestran efectos negativos menores en la salud y el bienestar psicológico (Haith-Cooper et al, 2018). Por el contrario, en el presente estudio, quienes realizan ejercicio físico dos veces o menos por semana no mostraron diferencias significativas con respecto al bienestar psicológico y la satisfacción con la vida.…”
unclassified